Aspiring to more? New evidence on the effect of a light-touch aspirations intervention in rural Ethiopia - Leight, Jessica; Gilligan, Daniel O.; Mulford, Michael; Taffesse, Alemayehu Seyoum; Tambet, Heleene (International Food Policy Research Institute, 2021)
A growing literature in economics has analyzed the effects of psychological interventions designed to boost individual aspirations as a strategy to increase investments with long-term returns and thus reduce poverty. This paper reports on a randomized controlled trial evaluating a short video-based intervention designed to increase aspirations of adults in poor rural Ethiopian households, all of whom are beneficiaries of the Productive Safety Net Program, the main government safety net program in Ethiopia. Evidence from a sample of 5258 adults from 3220 households is consistent with the hypothesis that there is no evidence that the aspirations treatment had any significant effects on self-reported aspirations for the household, educational investment in children, or savings nine months post-treatment, suggesting that the effect of light-touch aspirations treatments for extremely poor adults may be limited in this context.